THE THEORETICAL ESTIMATION OF THE COMPOSITION OF THE MELTED SLAGS SURFACE ASSOCIATES OF THE SYSTEM SiO2-CaO - V. F. Sobolev; N. V. Andrianov; A. A. Chichko (Литьë и металлургия)
The possibility of calculation of sectional areas of adsorbed on the surface of complexes in liquid cinders with formula SiO2 — CaO at basic capacity beyond unit is shown. The calculation is carried out in the framework of the method of molecular mechanics of structure and energies of possible silicooxygen anions. The theoretical estimation of supposition about participation of cyclic anion Si3O96- and its fluorsubstituted analogs in decrease of surface tension of melted slags CaO — SiO2 — CaF2 is carried out.